Finite time tracking control of higher order nonlinear multi agent systems with actuator saturation. Issue 3 (2016) - Mondal, Sanjoy; Su, Rong
Abstract: In this paper a distributed leader follower finite time tracking control of higher order nonlinear multi agent systems (MAS) is presented subject to actuator saturation. A saturated continuous homogeneous consensus control is developed to obtain finite time convergence. For stability of the saturated actuators the geometric homogeneity theory is used and it is proven that all the states of the followers can converge to that of the leader in finite time. Switching control is designed based on super twisting algorithm to nullify the effect of uncertainties and external disturbances. It is also ensures that the sliding surface reaches the equilibrium in finite time. The control law can be effectively used for more general higher order nonlinear agent dynamics. Simulation results verify the effectiveness of the proposed scheme.